Poor Nutritional Literacy and Relationship to Dietary Guideline Adherence in Inner-City Dialysis Patients. (14th June 2022) - Patel, Lekha; Wei, Lulu; Gidon, Ariel; Martinez-Machado, Sasha; Bae, Edward; Lee, Judy; Markell, Mariana
Abstract: Objectives: Poor nutritional literacy may influence understanding and adherence to dietary guidelines. We examined nutritional literacy and adherence to dietary guidelines in inner-city dialysis patients. Methods: A random sample of 34 dialysis pts was interviewed regarding knowledge about dietary guidelines and 24-hr food recall was recorded and analyzed using ASA-24. Nutritional literacy was assessed using the food label questionnaire. Results: Mean age was 56 ± 17,  58% (20) male, 88% (29) identified as Black, time on dialysis 64.1 ± 17.3 mos. Mean PO4 intake was 968.2 ± 111.9 mg,  sodium 2487 ± 240 mg,  potassium 1983 ± 222 mg. There was no association between age,  sex,  income or time on dialysis and adherence to dietary guidelines. All pts received monthly nutrition counseling. 18/24 (75%) pts said they did not know daily dietary sodium allowance, none answered correctly. 2/6 (33%) who stated they knew consumed <2300 mg while 8/18 (44%) who didn't know consumed less. Higher sodium intake in all groups correlated with fluid (r = 0.6, p = 0.002), PO4 (r = 0.8, p < 0.001), and potassium intake (r = 0.5, p = 0.007). 5/24 (21%) said they knew daily potassium allowance but 0% answered correctly. 20/24 (83%) pts didn't know how much PO4 to consume; 13/20 (65%) ate more than 800 mg phosphorus daily and none knew the recommended phosphorus recommendation. 18/24 (75%) pts stated they knew how much fluid they should drink per day and 9 (50%) pts were correct in their answer. Higher fluid intakes were associated with higher potassium (r = 0.54, p = 0.007), phosphorous (r = 0.41, p = 0.045) and sodium intakes (r = 0.6, p = 0.002). No pt scored in the adequate health literacy range by the food label test, with 21/24 (88%) scoring 0–1 (high risk) and 3/24 (12%) scoring 2–3 (moderate risk). Conclusions: In our population although patients report monthly nutrition counseling, the majority of could not recall the recommended dietary restrictions for sodium, potassium, PO4 or fluid. The majority of patients ate more than the recommended amounts for PO4 and sodium and those patients were less adherent to other dietary recommendations as well. All patients scored in the high to moderate risk category for nutritional literacy, which may explain inability to remember counseling recommendations and should be taken into account when designing educational programs. Funding Sources: Unfunded.